2009
DOI: 10.2967/jnumed.109.066498
|View full text |Cite
|
Sign up to set email alerts
|

11C-PK11195 PET for the In Vivo Evaluation of Neuroinflammation in the Rat Brain After Cortical Spreading Depression

Abstract: Neurogenic inflammation triggered by extravasation of plasma protein has been hypothesized as a key factor in the generation of the pain sensation associated with migraine. The principal immune cell that responds to this inflammation is the parenchymal microglia of the central nervous system. Methods: Using a PET technique with 11 , a PET ligand for peripheral type-benzodiazepine receptor, we evaluated the microglial activation in the rat brain after generation of unilateral cortical spreading depression, a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 40 publications
0
34
0
Order By: Relevance
“…Such neurogenic inflammation is thought to trigger a headache via stimulation of trigeminal afferents. Consistent with this hypothesis, cortical SD induced intracranial neurogenic inflammation around the meningeal blood vessels [13][14][15] , and subsequent activation of both peripheral [16] and central [17] trigeminal nociceptive pathways has been described. Here, we review the experimental evidence mainly from neurophysiological studies that has advanced the understanding of whether and how the neurovascular phenomenon of cortical SD causes intracranial neurogenic inflammation, and subsequently participates in triggering a migraine headache.…”
Section: Introductionmentioning
confidence: 55%
See 3 more Smart Citations
“…Such neurogenic inflammation is thought to trigger a headache via stimulation of trigeminal afferents. Consistent with this hypothesis, cortical SD induced intracranial neurogenic inflammation around the meningeal blood vessels [13][14][15] , and subsequent activation of both peripheral [16] and central [17] trigeminal nociceptive pathways has been described. Here, we review the experimental evidence mainly from neurophysiological studies that has advanced the understanding of whether and how the neurovascular phenomenon of cortical SD causes intracranial neurogenic inflammation, and subsequently participates in triggering a migraine headache.…”
Section: Introductionmentioning
confidence: 55%
“…Using [ 11 C]PK11195-PET imaging in rats, we demonstrated that unilateral cortical SD induces neurogenic inflammation in the ipsilateral cerebral hemisphere [14] . The highest [ 11 C]PK11195 radioactivity was seen in the initial area of the cortical SD (KCl-microinjected Yilong Cui, et al Role of cortical spreading depression in the pathophysiology of migraine 817 site), and moderate radioactivity was observed in the ipsilateral surrounding areas, but not in the corresponding contralateral areas.…”
Section: Rat Cerebral Cortexmentioning
confidence: 99%
See 2 more Smart Citations
“…One hypothesis states that the depolarization wave progressing through the cortex has a central role in migraine pathomechanism [24]. The excessive activation might well be enough to induce in cellular damage, [14] kindle neuroinflammation and consequently cause pain [84][85][86]. CSD in animals upregulates the matrix metalloproteinase (MMP)-9 [87] and the activation of MMP can elicit the leakage of blood-brain barrier and lead to inflammatory response and neuronal damage [88].…”
Section: The Relation Of Our Finding To Migraine Pathomechanismmentioning
confidence: 99%